The Level of Readiness of Misamis University in the Implementation of the New Curricula - Baluyos, Genelyn Rible; Toring, April Rose M.; Gahut, Marianne Jade C.; Tagaan, Dhanna Jean P.; Quiap, Kheleene Grace P.; Maliao, Honeymie A. (Universitas Negeri Semarang, 2020)
Curriculum change is one of the processes that help the school maintain its quality education. This study assessed the level of readiness on the implementation of the new curricula on the different programs in Misamis University during the first semester of SY 2018-2019 using a descriptive research design. A modified survey questionnaire adapted from the work of Espique (2018) was used to assess the level of readiness of the programs in the institution. The respondents included 60 teachers and 298 students chosen through purposive and stratified random sampling. Mean, standard deviation, and ANOVA or F-tests were the statistical tools used in the study. Results showed that the university was very highly ready for the implementation of the new curricula. Teachers and students perceived the level of readiness differently. Information about the new curricula must be disseminated well to the teachers, students, and benefactors. Abstrak Perubahan kurikulum merupakan satu proses yang membantu mengelola institusi pendidikan dalam meningkatkan kualitas pendidikannya. Penelitian ini mengkaji tingkat kesiapan implementasi kurikulum baru pada beberapa program studi yang berbeda di Universitas Miramis pada semester pertama tahun ajaran 2018-2019 menggunakan desain penelitian deskriptif. Kuesioner survei yang diadaptasi dari Espique (2018) digunakan dalam penelitian ini untuk mengetahui tingkat kesiapan beberapa program studi dan melibatkan 60 dosen dan 298 mahasiswa yang dipilih melalui purposive dan stratified random sampling dan datanya dianalisis menggunakan rata-rata, standar deviasi dan Anova atau F-test. Hasil penelitian menunjukkan bahwa program-program studi di Misamis sangat siap mengimplementasikan kurikulum baru. Dosen dan siswa memahami level kesiapan secara berbeda dan menunjukkan bahwa kurikulum baru hendaknya disebarkan dengan baik kepada para dosen, mahasiswa, dan donatur.